Role of early warning signs in children with severe dengue infection - Pothapregada, Sriram; Sivapurapu, Vijayalakshmi; Kamalakannan, Banupriya; Thulasingham, Mahalakshmy (International Journal of Contemporary Pediatrics, 2018)
Background: The objective of the study was to evaluate and analyze the role of preceding early warning signs at admission in children with severe dengue infection. Methods: All children (0-12 y of age) diagnosed and confirmed as dengue fever admitted at a tertiary care hospital at Puducherry were retrospectively analysed from hospital case records as per the revised World Health Organization(WHO) guidelines 2009 for dengue fever. The data was analysed by descriptive statistics using SPSS 16.0 statistical software. Early warning signs were analyzed by logistic regression and a P-value of <0.05 was taken as significant. Results: Out of 360 children confirmed with diagnosis of dengue fever, non-severe and severe dengue infection was seen in 214(59.4%) and 146 cases (40.6%) respectively. The most common manifestation of severe dengue infection were shock (40.6%), bleeding (16.7%) and multiorgan failure (2.2%). On logistic regression, the warning signs most commonly associated with severe dengue infection were pain abdomen, hepatomegaly, hypotension at admission and HCT>20% with concomitant platelet<50,000/mm3. Clinical variables which were unlisted in the revised guidelines but significantly associated with severe dengue infection were Age >6 yrs, retro-orbital pain, palmar erythema, joint pain, splenomegaly, positive tourniquet test, right hypochondriac pain and epigastric tenderness. Conclusions: Early identification of the preceding warning signs, timely intervention and vigilant monitoring can reduce the morbidity and mortality in children with severe dengue infection. Since there were other clinical variables not enlisted as warning signs but were significantly associated with severe dengue infection, the list of warning signs in the revised guidelines needs to be expanded.